PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 15 PADANG - Yulia Putri, Nia; Tanjung, Mirna; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACT Â This study aims to analyze : 1 ) the effect of parental education on learning outcomes of students of class X in subjects Economics in SMAN 15 Padang , 2 ) the influence of independent learning on learning outcomes of students of class X in subjects Economics in SMAN 15 Padang 3) influence the level of parental education and independence against a class X student learningÂ  outcomes in subjects Economics in SMAN 15 Padang. When the study was conducted in January 2014 . Research used in this study is a descriptive study associative . The study population was all students of class X SMA Negeri 15 Padang numbered 284 people . Sampling technique with proportional random sampling with a sample size of 99 people . Data analysis techniques : descriptive analysis and inductive analysis , namely normality test, heteroscedasticity, multikoleniaritas tes , autocorrelation test and multiple regression analysis with SPSS version 16.0. The results showed that : 1 ) there is a positive and significant effect of the level of parental education on learning outcomes of students of class X in subjects Economics based on the results of the analysis of data obtained value of t > t table ( 6.220 > 1.66 ) , there is positive and significant between independent learning on learning outcomes of students of class X in subjects Economics based on the results of the analysis of data obtained value of t > t table ( 3.517 > 1.66 ) , there is positive and significant co- operation between the level of parental education and independent learning on learning outcomes class X on economic subjects on SMAN 15 Champaign school year 2013/2014 based on data analysis of F > Ftable ( 31.678 > 3.09 ) and R Square 0.398 means the ability of a variable level of parental education and independent learning in explaining the outcome variables studied amounted to 39.80 % .Based on the research results , it is expected that parents can guide students to learn at home in order to increase learning outcomes and teachers are also expected to provide a boost for students to learn independently by providing structured tasks every meeting.